1992
DOI: 10.1101/gad.6.6.965
|View full text |Cite
|
Sign up to set email alerts
|

A novel modulator domain of Ets transcription factors.

Abstract: The ets gene family is composed of several oncogenes and codes for transcription factors. The Ets proteins have a similar sequence called the ets domain and bind to the core motif A/CGGAA. We show here that several members of the ets family have different trans-activating properties. The ets domain of Ets-1 is required for DNA binding. Adjacent to this domain there is a novel element that inhibits DNA binding. It appears to alter the structure of the DNA-binding domain before it interacts with DNA. There is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 30 publications
6
139
0
Order By: Relevance
“…[17][18][19][20] The ets family of transcription factors has a DNA-binding domain in common that binds to a core GGA(A/T) DNA sequence. 21,22 In situ hybridization studies have shown that the proto-oncogene c-ets is expressed in endothelial cells at the beginning of blood vessel formation, under normal and pathological conditions. 23,24 Thus, previous reports suggest that the ets family may activate the transcription of genes encoding collagenase 1, stromelysine 1 and urokinase plasminogen activator, which are proteases involved in extracellular matrix degradation.…”
Section: Figure 3 Effect Of the Transfection Of Hgf Vector On The Vasmentioning
confidence: 99%
“…[17][18][19][20] The ets family of transcription factors has a DNA-binding domain in common that binds to a core GGA(A/T) DNA sequence. 21,22 In situ hybridization studies have shown that the proto-oncogene c-ets is expressed in endothelial cells at the beginning of blood vessel formation, under normal and pathological conditions. 23,24 Thus, previous reports suggest that the ets family may activate the transcription of genes encoding collagenase 1, stromelysine 1 and urokinase plasminogen activator, which are proteases involved in extracellular matrix degradation.…”
Section: Figure 3 Effect Of the Transfection Of Hgf Vector On The Vasmentioning
confidence: 99%
“…However, amino acids highly conserved amongst ETS family members (Janknecht and Nordheim, 1993) are well conserved in ELF5 (23/38). Some of these highly conserved residues, such as the three tryptophan residues in the carboxyl half of the ETS domain, have been demonstrated to be structurally critical for DNA binding of other ETS family members (Wang et al, 1992;Wasylyk et al, 1992).…”
Section: Comparison Of Human and Mouse Elf5 Amino Acid Sequencesmentioning
confidence: 99%
“…Both 42 kDa and 51 kDa ETS1 bind to DNA with similar a nity and dissociate at di erent rates (Fisher et al, 1994). P42-ETS1 lacks the inhibitory domain involved in the intramolecular folding (Wasylyk et al, 1992;Jonsen et al, 1996). Furthermore, phosphorylation of ETS1 has been shown to inhibit its DNA binding properties (Rabault and Ghysdael, 1995;Fisher et al, 1994).…”
Section: Introductionmentioning
confidence: 99%